Porous nickel-based amorphous alloy capable of being used for high-sensitivity glucose sensing and preparation method of porous nickel-based amorphous alloy

By developing porous nickel-based amorphous alloy materials, amorphous bands with micron-scale pores or channel morphology are formed using induction smelting and electrochemical dealloyment processes, the stability and cost problems of existing glucose sensor materials are solved, and the glucose detection effect with high sensitivity and low cost is achieved.

CN119736561APending Publication Date: 2025-04-01NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411937666.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing glucose sensor materials have shortcomings in terms of stability and cost, especially enzyme sensors are susceptible to the environment and have high costs, while the sensitivity and stability of non-enzymatic electrochemical sensor materials need to be improved.

Method used

A porous nickel-based amorphous alloy material was developed, and prepared by induction smelting, single-roll belt swing method and electrochemical dealloyment process to form amorphous strip with micron-scale holes or channel morphology to improve the specific surface area and electrochemical activity of the material.

Benefits of technology

It realizes high-sensitivity glucose detection, low cost and high electrochemical performance, and is suitable for non-enzymatic electrochemical glucose sensors, significantly improving the detection sensitivity and stability of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736561A_ABST
    Figure CN119736561A_ABST
Patent Text Reader

Abstract

The invention discloses a porous nickel-based amorphous alloy capable of being used for high-sensitivity glucose sensing and a preparation method of the porous nickel-based amorphous alloy. The method comprises the following steps: weighing raw materials according to a formula, preliminarily preparing as-cast nickel-based alloy through vacuum induction melting, then purifying an alloy ingot by utilizing a melting coating process, and finally preparing the nickel-based amorphous alloy strip in an argon atmosphere by adopting a single-roller rotary quenching method. And then, carrying out corrosion regulation and control on the strip through electrochemical surface treatment to form a uniformly distributed micron-sized porous structure or interconnected channel morphology. The prepared amorphous alloy strip has a non-periodic atomic structure and enriched unsaturated active sites, the surface energy state and the electrochemical activity are further improved in combination with the morphology of micron-sized holes or interconnected channels formed by electrochemical dealloying, and excellent glucose detection performance is shown; the method has the advantages of high sensitivity, low detection limit and wide linear detection range, and provides a new way for the development of low-cost and high-performance non-enzymatic electrochemical glucose sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the preparation of amorphous alloys and the technical field of electrochemical glucose detection, and in particular to a porous nickel-based amorphous alloy that can be used for high-sensitivity glucose sensing and a preparation method thereof. Specifically, the present invention combines the material advantages of amorphous structure and porous channel morphology to develop a nickel-based amorphous alloy material with high surface activity, high electrochemical performance and low cost, which is suitable for the field of non-enzymatic electrochemical glucose sensors. Background Art

[0002] With the aging of the global population and changes in lifestyle, diabetes has become a serious public health problem worldwide. It is predicted that by 2030, the number of diabetes patients worldwide will reach 366 million. Diabetes not only seriously affects the quality of life of patients, but also easily causes cardiovascular disease, renal failure, retinopathy and other complications, which puts tremendous pressure on personal health and the global medical system. Therefore, achieving fast, accurate and stable blood sugar monitoring is crucial for the early diagnosis, management and complication prevention of diabetes.

[0003] Although traditional enzyme glucose sensors have high sensitivity, their enzyme activity is easily affected by external environments such as temperature, humidity and pH value, resulting in poor stability and repeatability, which limits their wide application. To overcome these defects, non-enzymatic electrochemical glucose sensors have gradually become the focus of research due to their advantages such as strong stability, fast response and simple operation. Among them, transition metal elements such as Ni, Co, Fe, Cu, etc. have become ideal electrode materials due to their abundant reserves, low cost and excellent electrochemical properties. Among many non-enzymatic sensor materials, amorphous alloys have excellent electrochemical activity due to their unique non-periodic atomic structure and high concentration of unsaturated active sites, which are significantly better than crystalline materials. In addition, to further improve the performance of glucose sensors, electrochemical dealloying method, as an effective means of surface microstructure regulation, can selectively dissolve some metal elements to form interconnected porous morphology on the alloy surface. This structure not only significantly increases the specific surface area of ​​the material, exposes more active sites, but also facilitates the rapid adsorption and catalytic reaction of glucose molecules, thereby significantly improving the sensitivity and electrochemical performance of the sensor.

[0004] Therefore, the development of high-performance glucose sensors based on transition metal amorphous alloys and constructed through electrochemical dealloying technology has become a feasible path to solve the current problems of stability and cost of detection materials. Summary of the invention

[0005] Based on the above, the present invention proposes a porous nickel-based amorphous alloy that can be used for high-sensitivity glucose sensing and a preparation method thereof, providing a nickel-based amorphous alloy material with low cost and high glucose detection sensitivity.

[0006] The technical solution for achieving the purpose of the present invention is:

[0007] A porous nickel-based amorphous strip with micron-scale holes or channels on the surface, and its initial composition is Ni a TM b P c B d , where TM is a transition metal element, a, b, c, and d are all atomic ratios, 2≤(a+b) / (c+d)≤6.

[0008] The preparation method of the porous nickel-based amorphous strip comprises the following specific steps:

[0009] In the first step, the single-element raw materials are weighed according to the initial component atomic ratio of the target amorphous alloy and placed in an induction melting furnace for preliminary alloying;

[0010] In the second step, boron oxide is added to the glass tube and the temperature is raised to 1000°C along with the muffle furnace, and the alloy ingot obtained in the first step is added, and the temperature is continued to be above the melting point of the alloy, and then the temperature is kept for a period of time and then quickly cooled with water;

[0011] The third step is to put the alloy ingot obtained in the second step into a glass tube with a well-ground hole and put it into a vacuum belt spinning machine. The molten high-temperature metal liquid is quickly cooled by a high-speed rotating copper roller to form an amorphous strip.

[0012] In the fourth step, the amorphous strip obtained in the third step is electrochemically dealloyed in an acidic solution using an electrochemical workstation, and then cleaned and dried to obtain a strip with micron-scale holes or channel morphology.

[0013] Preferably, the purity of the single substance raw material is 99.0-99.999%, and the metal raw material is ground to remove the oxide layer and washed with anhydrous ethanol and dried before being weighed.

[0014] Preferably, in the first step, the induction melting current is 20-60A.

[0015] Preferably, in the third step, the induction melting current is 20-60A, and the copper roller speed is above 4000 rpm.

[0016] Preferably, in the fourth step, the pH value of the acidic solution is less than 4, the acidic solution is a mixed solution of sulfuric acid and phosphoric acid, the molar ratio of phosphoric acid to sulfuric acid is 1:4, and the applied voltage is greater than the corrosion starting potential.

[0017] The porous nickel-based amorphous strip electrode material used in the present invention has significant advantages in electrochemical glucose detection and has high sensitivity and low detection limit compared with other materials.

[0018] Compared with the existing technology, the present invention has the following advantages and effects:

[0019] (1) High-energy structure and excellent electrochemical activity: The unique non-periodic atomic structure of the amorphous strips gives the material higher surface free energy and abundant unsaturated active sites, which helps to improve the electrochemical reaction activity; in addition, through the electrochemical dealloying process, micron-scale interconnected pores are formed on the surface, which effectively increases the specific surface area and the number of active sites of the material, significantly improving the electrocatalytic oxidation performance of glucose;

[0020] (2) Simple process and controllable structure: The present invention adopts simple processes such as induction melting, single-roller strip spinning method and electrochemical dealloying, and the preparation process is efficient and controllable. The obtained amorphous strip has uniform structure, adjustable size and clean surface. In addition, the corrosion process forms a uniformly distributed porous structure by precisely controlling the corrosion voltage and time, which meets the needs of different applications.

[0021] (3) Low cost and potential for large-scale application: With transition metal elements such as nickel as the main raw materials, the material of the present invention has low cost and abundant resources, and is suitable for large-scale preparation and promotion and application; compared with precious metal-based electrode materials, amorphous alloys are not only lower in cost, but also have excellent electrochemical stability and reusability, making them an ideal choice for realizing high-performance, low-cost glucose sensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 X-ray diffraction patterns of the nickel-based amorphous strips prepared in Examples 1-4 of the present invention.

[0023] Figure 2 These are scanning electron microscope images of the porous nickel-based amorphous strips prepared in Examples 2-4 of the present invention, (a) is the SEM image of the sample in Example 2 at a magnification of 40,000 times, (b) is the SEM image of the sample in Example 3 at a magnification of 20,000 times, and (c) is the SEM image of the sample in Example 4 at a magnification of 20,000 times.

[0024] Figure 3 The constant potential glucose titration test diagrams of the nickel-based amorphous strips as the working electrode in Examples 1-4 of the present invention are shown in the inset, and the glucose detection sensitivity test diagram is shown in the inset. (a) is the electrochemical test diagram of the sample in Example 1, (b) is the electrochemical test diagram of the sample in Example 2, (c) is the electrochemical test diagram of the sample in Example 3, and (d) is the electrochemical test diagram of the sample in Example 4.

[0025] Table 1 is the EDS composition statistics of the nickel-based amorphous strips prepared in Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described below by specific implementation methods. All embodiments are based on the technical solution of the present invention, and the implementation process and specific operation steps are described in detail. However, it should be understood that the protection scope of the present invention is not limited to the following embodiments.

[0027] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0028] Example 1

[0029] This embodiment prepares Ni with a width of about 1.5 mm and a thickness of 20-30 μm. 40 Fe 40 P 14 B 6 Amorphous strips.

[0030] The preparation method of this embodiment comprises the following steps:

[0031] Step 1: Surface treatment of Ni, Fe, P, and B raw materials, removal of oxide film and cleaning with anhydrous ethanol to ensure the cleanliness of the material surface. 40 Fe 40 P 14 B 6 Weigh each raw material accurately in proportion to the components and set aside.

[0032] Step 2: Put the four raw materials obtained in step 1 into a glass tube and then place them together in a high vacuum induction melting furnace. Reduce the oxygen content in the chamber through multiple gas filling and degassing operations to reduce oxidized impurities. Then, adjust the appropriate current for multiple smelting to completely melt the materials and mix them evenly, and finally obtain an alloy ingot.

[0033] Step 3, placing the alloy ingot obtained in step 2 together with the boron oxide coating agent in a clean glass tube, heating to above the melting point of the alloy, and maintaining a low vacuum state for heat preservation. After the heat preservation is completed, the glass tube is quickly taken out and cooled in cold water, and the alloy ingot is further purified to improve the purity.

[0034] Step 4: Put the alloy ingot purified in step 3 into a glass tube with a small hole and put it into a vacuum belt spinning machine. The alloy ingot is induction-smelted into molten alloy liquid under a certain current, and the molten alloy is sprayed through the small hole of the glass tube onto a high-speed rotating copper roller by using the air pressure difference, and then quickly cooled and thrown out under centrifugal action to make Ni 40 Fe 40 P 14 B 6 Amorphous alloy strips. The amorphous properties of the obtained material are shown by X-ray diffraction patterns (e.g. Figure 1 The actual components detected by EDS are listed in Table 1.

[0035] Step 5: Ni prepared in step 4 40 Fe 40 P 14 B 6 Electrochemical tests were performed using amorphous alloy as electrode material. First, 0.1 mol / L NaOH solution was prepared and poured into a five-necked flask to build a three-electrode system with Ni 40 Fe 40 P 14 B 6 The amorphous alloy strip was used as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode. Then the electrochemical workstation was connected to perform a constant potential glucose titration test. Figure 3 As shown in (a), the test voltage is maintained at 540 mV, and the current generated by the electrode is recorded. Subsequently, the glucose concentration in the electrolyte solution is adjusted (0.01 mmol / L to 10 mmol / L) by gradually adding glucose to the NaOH solution in the five-necked flask to simulate a stepwise change in glucose concentration. The specific titration concentrations are: 0.01mmol / L, 0.02mmol / L, 0.03mmol / L, 0.04mmol / L, 0.05mmol / L, 0.06mmol / L, 0.07mmol / L, 0.08mmol / L, 0.09mmol / L, 0.1mmol / L, 0.2mmol / L, 0.3mmol / L, 0.4mmol / L, 0.5mmol / L, 0.6mmol / L, 0.7mmol / L, 0.8mmol / L, 0.9mmol / L, 1mmol / L, 1.5mmol / L, 2mmol / L, 2.5mmol / L, 3mmol / L, 3.5mmol / L, 4mmol / L, 4.5mmol / L, 5mmol / L, 6mmol / L, 7mmol / L, 8mmol / L, 9mmol / L and 10mmol / L. The current changes of the working electrode were monitored and recorded in real time by an electrochemical workstation to analyze the electrocatalytic oxidation ability of the material on glucose, such as Figure 3 The inset in a shows the glucose sensitivity of the material. -2 mM -1 The detection limit was 0.41 μmol / L and the linear range was 0.01-2 mmol / L.

[0036] Example 2

[0037] This embodiment prepares a porous NiFePB amorphous strip with a width of about 1.5 mm and a thickness of 20-30 μm.

[0038] The preparation method of this embodiment comprises the following steps:

[0039] Step 1: Surface treatment of Ni, Fe, P, and B raw materials, removal of oxide film and cleaning with anhydrous ethanol to ensure the cleanliness of the material surface. 40 Fe 40 P 14 B 6 Weigh each raw material accurately in proportion to the components and set aside.

[0040] Step 2: Put the four raw materials obtained in step 1 into a glass tube and then place them together in a high vacuum induction melting furnace. Reduce the oxygen content in the chamber through multiple gas filling and degassing operations to reduce oxidized impurities. Then, adjust the appropriate current for multiple smelting to completely melt the materials and mix them evenly, and finally obtain an alloy ingot.

[0041] Step 3, placing the alloy ingot obtained in step 2 together with the boron oxide coating agent in a clean glass tube, heating to above the melting point of the alloy, and maintaining a low vacuum state for heat preservation. After the heat preservation is completed, the glass tube is quickly taken out and cooled in cold water, and the alloy ingot is further purified to improve the purity.

[0042] Step 4: The alloy ingot purified in step 3 is loaded into a glass tube with a small hole and placed in a vacuum belt spinning machine. The alloy ingot is induction-smelted into a molten alloy liquid under a certain current, and the molten alloy is sprayed through the small hole of the glass tube onto a high-speed rotating copper roller by using the air pressure difference, and is quickly cooled and thrown out under the action of centrifugation to produce a NiFePB amorphous alloy strip.

[0043] Step 5: The NiFePB amorphous strip obtained in step 4 is subjected to electrochemical dealloying in a mixed solution of sulfuric acid and phosphoric acid using an electrochemical workstation. The test adopts a three-electrode system, with the sample as the working electrode, the graphite sheet as the counter electrode, and Hg / Hg 2 SO 4 The reference electrode was used. During the treatment, a constant voltage of -600 mV (relative to Hg / Hg 2 SO 4 The reference electrode) was used and the etching time was set to 1 hour. After treatment, the strips with micron-sized holes were obtained by washing and drying. The amorphous properties of the obtained material were confirmed by X-ray diffraction patterns (e.g. Figure 1 The surface morphology was confirmed by scanning electron microscopy (as shown in Figure 2 The strips were characterized by a hole with a size of 0.1 to 0.2 μm. The actual components detected by EDS are listed in Table 1.

[0044] Step 6: Conduct electrochemical tests using the porous NiFePB amorphous alloy obtained in step 5 as the electrode material. First, prepare a 0.1 mol / L NaOH solution and pour it into a five-necked flask to build a three-electrode system, using the porous NiFePB amorphous alloy as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode. Then connect the electrochemical workstation to conduct a constant potential glucose titration test. Figure 3 As shown in (b), the test voltage is kept constant and the current generated by the electrode is recorded. Subsequently, the glucose concentration in the electrolyte solution is adjusted (0.01 mmol / L to 10 mmol / L) by gradually adding glucose to the NaOH solution in the five-necked flask to simulate the step-by-step change of glucose concentration. The specific titration concentrations are: 0.01mmol / L, 0.02mmol / L, 0.03mmol / L, 0.04mmol / L, 0.05mmol / L, 0.06mmol / L, 0.07mmol / L, 0.08mmol / L, 0.09mmol / L, 0.1mmol / L, 0.2mmol / L, 0.3mmol / L, 0.4mmol / L, 0.5mmol / L, 0.6mmol / L, 0.7mmol / L, 0.8mmol / L, 0.9mmol / L, 1mmol / L, 1.5mmol / L, 2mmol / L, 2.5mmol / L, 3mmol / L, 3.5mmol / L, 4mmol / L, 4.5mmol / L, 5mmol / L, 6mmol / L, 7mmol / L, 8mmol / L, 9mmol / L and 10mmol / L. The current changes of the working electrode were monitored and recorded in real time by an electrochemical workstation to analyze the electrocatalytic oxidation ability of the material on glucose, such as Figure 3 As shown in the inset of b, the glucose sensitivity of this material is 2.218 mA cm -2 (mmol / L) -1 The detection limit was 1.16 μmol / L and the linear range was 0.01-2.5 mmol / L.

[0045] Example 3

[0046] This embodiment prepares a NiFePB amorphous strip having a width of about 1.5 mm and a thickness of 10-20 μm with an interconnected channel surface morphology.

[0047] The preparation method of this embodiment comprises the following steps:

[0048] Step 1: Surface treatment of Ni, Fe, P, and B raw materials, removal of oxide film and cleaning with anhydrous ethanol to ensure the cleanliness of the material surface. 40 Fe 40 P 14 B6 Weigh each raw material accurately in proportion to the components and set aside.

[0049] Step 2: Put the four raw materials obtained in step 1 into a glass tube and then place them together in a high vacuum induction melting furnace. Reduce the oxygen content in the chamber through multiple gas filling and degassing operations to reduce oxidized impurities. Then, adjust the appropriate current for multiple smelting to completely melt the materials and mix them evenly, and finally obtain an alloy ingot.

[0050] Step 3, placing the alloy ingot obtained in step 2 together with the boron oxide coating agent in a clean glass tube, heating to above the melting point of the alloy, and maintaining a low vacuum state for heat preservation. After the heat preservation is completed, the glass tube is quickly taken out and cooled in cold water, and the alloy ingot is further purified to improve the purity.

[0051] Step 4: The alloy ingot purified in step 3 is loaded into a glass tube with a small hole and placed in a vacuum belt spinning machine. The alloy ingot is induction-smelted into a molten alloy liquid under a certain current, and the molten alloy is sprayed through the small hole of the glass tube onto a high-speed rotating copper roller by using the air pressure difference, and is quickly cooled and thrown out under the action of centrifugation to produce a NiFePB amorphous alloy strip.

[0052] Step 5: The NiFePB amorphous strip obtained in step 4 is subjected to electrochemical dealloying in a mixed solution of sulfuric acid and phosphoric acid using an electrochemical workstation. The test adopts a three-electrode system, with the sample as the working electrode, the graphite sheet as the counter electrode, and Hg / Hg 2 SO 4 The reference electrode was used. During the treatment, a constant voltage of -550 mV (relative to Hg / Hg 2 SO 4 The reference electrode) was used, and the etching time was set to 1 hour. After treatment, the strips were cleaned and dried to obtain the surface morphology of interconnected channels. The amorphous properties of the obtained material were confirmed by X-ray diffraction patterns (such as Figure 1 The surface morphology was confirmed by scanning electron microscopy (as shown in Figure 2 b) shows that the strips after treatment have channels with a width of 0.1 to 0.2 microns. The actual components detected by EDS are listed in Table 1.

[0053] Step 6, using the NiFePB amorphous alloy with interconnected channel surface morphology obtained in step 5 as the electrode material for electrochemical testing. First, prepare a 0.1 mol / L NaOH solution and pour it into a five-necked flask to build a three-electrode system, using the NiFePB amorphous alloy as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode. Then connect the electrochemical workstation to perform a constant potential glucose titration test, such as Figure 3c, the test voltage was kept constant and the current generated by the electrode was recorded. Subsequently, the glucose concentration in the electrolyte solution was adjusted (0.01 mmol / L to 10 mmol / L) by gradually adding glucose to the NaOH solution in the five-necked flask to simulate the stepwise change of glucose concentration. The specific titration concentrations are: 0.01mmol / L, 0.02mmol / L, 0.03mmol / L, 0.04mmol / L, 0.05mmol / L, 0.06mmol / L, 0.07mmol / L, 0.08mmol / L, 0.09mmol / L, 0.1mmol / L, 0.2mmol / L, 0.3mmol / L, 0.4mmol / L, 0.5mmol / L, 0.6mmol / L, 0.7mmol / L, 0.8mmol / L, 0.9mmol / L, 1mmol / L, 1.5mmol / L, 2mmol / L, 2.5mmol / L, 3mmol / L, 3.5mmol / L, 4mmol / L, 4.5mmol / L, 5mmol / L, 6mmol / L, 7mmol / L, 8mmol / L, 9mmol / L and 10mmol / L. The current changes of the working electrode were monitored and recorded in real time by an electrochemical workstation to analyze the electrocatalytic oxidation ability of the material on glucose, such as Figure 3 As shown in the inset of c, the glucose sensitivity of this material is 1.684 mA cm -2 (mmol / L) -1 The detection limit was 1.92 μmol / L and the linear range was 0.01-2.5 mmol / L.

[0054] Example 4

[0055] This embodiment prepares a NiFePB amorphous strip having a width of about 1.5 mm and a thickness of 10-20 μm with an interconnected channel surface morphology.

[0056] The preparation method of this embodiment comprises the following steps:

[0057] Step 1: Surface treatment of Ni, Fe, P, and B raw materials, removal of oxide film and cleaning with anhydrous ethanol to ensure the cleanliness of the material surface. 40 Fe 40 P 14 B 6 Weigh each raw material accurately in proportion to the components and set aside.

[0058] Step 2: Put the four raw materials obtained in step 1 into a glass tube and then place them together in a high vacuum induction melting furnace. Reduce the oxygen content in the chamber through multiple gas filling and degassing operations to reduce oxidized impurities. Then, adjust the appropriate current for multiple smelting to completely melt the materials and mix them evenly, and finally obtain an alloy ingot.

[0059] Step 3, placing the alloy ingot obtained in step 2 together with the boron oxide coating agent in a clean glass tube, heating to above the melting point of the alloy, and maintaining a low vacuum state for heat preservation. After the heat preservation is completed, the glass tube is quickly taken out and cooled in cold water, and the alloy ingot is further purified to improve the purity.

[0060] Step 4: The alloy ingot purified in step 3 is loaded into a glass tube with a small hole and placed in a vacuum belt spinning machine. The alloy ingot is induction-smelted into a molten alloy liquid under a certain current, and the molten alloy is sprayed through the small hole of the glass tube onto a high-speed rotating copper roller by using the air pressure difference, and is quickly cooled and thrown out under the action of centrifugation to produce a NiFePB amorphous alloy strip.

[0061] Step 5: The NiFePB amorphous strip obtained in step 4 is subjected to electrochemical dealloying in a mixed solution of sulfuric acid and phosphoric acid using an electrochemical workstation. The test adopts a three-electrode system, with the sample as the working electrode, the graphite sheet as the counter electrode, and Hg / Hg 2 SO 4 The reference electrode is used. During the treatment, a constant voltage of -500 mV (relative to Hg / Hg 2 SO 4 The reference electrode) was used, and the etching time was set to 1 hour. After treatment, the strips were cleaned and dried to obtain the surface morphology of interconnected channels. The amorphous properties of the obtained material were confirmed by X-ray diffraction patterns (such as Figure 1 The surface morphology was confirmed by scanning electron microscopy (as shown in Figure 2 c) characterization, the strips after treatment have channels with a width of 0.1 to 0.3 microns. The actual components detected by EDS are listed in Table 1.

[0062] Step 6, using the NiFePB amorphous alloy with interconnected channel surface morphology obtained in step 5 as the electrode material for electrochemical testing. First, prepare a 0.1 mol / L NaOH solution and pour it into a five-necked flask to build a three-electrode system, using the NiFePB amorphous alloy as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode. Then connect the electrochemical workstation to perform a constant potential glucose titration test, such as Figure 3d, the test voltage was kept constant and the current generated by the electrode was recorded. Subsequently, the glucose concentration in the electrolyte solution was adjusted (0.01 mmol / L to 10 mmol / L) by gradually adding glucose to the NaOH solution in the five-necked flask to simulate the step-by-step change of glucose concentration. The specific titration concentrations are: 0.01mmol / L, 0.02mmol / L, 0.03mmol / L, 0.04mmol / L, 0.05mmol / L, 0.06mmol / L, 0.07mmol / L, 0.08mmol / L, 0.09mmol / L, 0.1mmol / L, 0.2mmol / L, 0.3mmol / L, 0.4mmol / L, 0.5mmol / L, 0.6mmol / L, 0.7mmol / L, 0.8mmol / L, 0.9mmol / L, 1mmol / L, 1.5mmol / L, 2mmol / L, 2.5mmol / L, 3mmol / L, 3.5mmol / L, 4mmol / L, 4.5mmol / L, 5mmol / L, 6mmol / L, 7mmol / L, 8mmol / L, 9mmol / L and 10mmol / L. The current changes of the working electrode were monitored and recorded in real time by an electrochemical workstation to analyze the electrocatalytic oxidation ability of the material on glucose, such as Figure 3 As shown in the inset in d, the glucose sensitivity of this material is 0.441 mA cm -2 (mmol / L) -1 The detection limit was 1.18 μmol / L and the linear range was 0.01-1.5 mmol / L.

[0063] According to the EDS composition statistics and scanning electron microscopy results of Examples 1-4, the electrochemical dealloying treatment has a significant regulatory effect on the chemical composition and surface morphology of the nickel-iron-based amorphous alloy, which directly affects the electrochemical properties of the material. Table 1 shows that as the dealloying voltage increases, the dissolution rate of metal elements (such as Ni and Fe) increases significantly, while the oxide content gradually increases, and the surface morphology gradually evolves from a uniformly distributed micron-scale porous structure to an interconnected channel morphology ( Figure 2 ).

[0064] The performance of the material in glucose electrochemical tests ( Figure 3) were analyzed and it was found that the optimal dealloying voltage was -600mV. Under this condition, a uniform micron-sized porous structure was formed on the surface of the material, the dissolution of Ni and Fe elements was moderate, and the oxide content was reasonably controlled. This optimized surface morphology not only significantly increases the specific surface area, but also retains abundant active sites, while avoiding the adverse effects of excessive oxide generation on conductivity, thereby achieving excellent electrochemical performance. In contrast, under higher voltage conditions (such as -550mV or -500mV), the rapid dissolution of the metal and the excessive generation of oxides weakened the catalytic activity of the material, resulting in a significant decrease in the electrochemical performance.

[0065] The present invention achieves effective regulation of the surface morphology and chemical composition of nickel-iron-based amorphous alloys by optimizing the electrochemical dealloying process, especially the precise control of the applied voltage. The samples treated at -600mV form a uniform micron porous structure and an appropriate oxide layer, which significantly improves their electrocatalytic performance, showing high sensitivity, wide linear range and good stability, providing a scientific basis and technical support for the development of high-performance non-enzymatic electrochemical glucose sensors.

[0066] Table 1

[0067]

Claims

1. A porous nickel-based amorphous alloy for high-sensitivity glucose sensing, characterized in that: The porous nickel-based amorphous alloy is composed of Ni a TM b P c B d , where TM is a transition metal element, a, b, c, and d are all atomic ratios, 2≤(a+b) / (c+d)≤6, the strip width is 1-3mm, and the thickness is about 10-50μm.

2. The porous nickel-based amorphous alloy according to claim 1, characterized in that: The nickel-based amorphous alloy strip preparation process comprises the following steps: In the first step, the single element raw materials are weighed according to the designed atomic ratio and then preliminarily alloyed by induction melting; In the second step, boron oxide is added to the glass tube and the temperature is raised to 1000°C along with the muffle furnace. The alloy ingot obtained in the first step is added to the glass tube, and the temperature is continued to be above the melting point of the alloy. After keeping the temperature for a period of time, the alloy is quickly cooled by water. In the third step, the alloy ingot obtained in the second step is loaded into a glass tube with a grinding hole and placed in a vacuum belt spinning machine. The molten high-temperature metal liquid is quickly cooled by a high-speed rotating copper roller to form an amorphous strip.

3. The porous nickel-based amorphous alloy according to claim 2, characterized in that: In the second step, the holding temperature is 1200°C and the holding time is 3h.

4. The porous nickel-based amorphous alloy according to claim 2, characterized in that: In the third step, the induction melting current is 20-60A, and the copper roller speed is above 4000 rpm.

5. The porous nickel-based amorphous alloy according to claim 1 or 2, characterized in that: The amorphous strip is electrochemically dealloyed in an acidic solution using an electrochemical workstation, and then cleaned and dried to obtain a porous nickel-based amorphous alloy strip with micron-scale holes or channel morphology.

6. A method for preparing a porous nickel-based amorphous alloy for high-sensitivity glucose sensing according to any one of claims 1 to 5, characterized in that: The nickel-based amorphous alloy strip preparation process comprises the following steps: In the first step, the single element raw materials are weighed according to the designed atomic ratio and then preliminarily alloyed by induction melting; In the second step, boron oxide is added to the glass tube and the temperature is raised to 1000°C along with the muffle furnace. The alloy ingot obtained in the first step is added to the glass tube, and the temperature is continued to be above the melting point of the alloy. After keeping the temperature for a period of time, the alloy is quickly cooled by water. The third step is to put the alloy ingot obtained in the second step into a glass tube with a grinding hole and put it into a vacuum belt spinning machine. The molten high-temperature metal liquid is quickly cooled by a high-speed rotating copper roller to form an amorphous strip. In the fourth step, the amorphous strip obtained in the third step is electrochemically dealloyed in an acidic solution using an electrochemical workstation, and then cleaned and dried to obtain a porous nickel-based amorphous alloy strip with micron-scale holes or channel morphology.

7. The preparation method according to claim 6, characterized in that: In the fourth step, a voltage greater than the corrosion initiation potential is applied to the electrodes.

8. The method according to claim 6, characterized in that In the fourth step, the pH value of the acidic solution is less than 4, the acidic solution is a mixed solution of sulfuric acid and phosphoric acid, and the molar ratio of phosphoric acid to sulfuric acid is 1:

4.

9. A use of the nickel-based amorphous alloy amorphous strip electrode material according to claims 1-5, characterized in that: Glucose was detected using a three-electrode system, with a nickel-based amorphous alloy strip as the working electrode, a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode. The sensing performance of the material was evaluated by a constant potential glucose titration test in an alkaline environment, thereby accurately characterizing its electrochemical response characteristics in glucose detection.